Georgia Library Association Handbook - Georgia Library Association (University of Georgia Libraries, 2021)
This handbook exists to help GLA members in carrying out the activities of the organization with clarity and continuity. Please contact the Handbook Committee if you know of changes that need to be made or if you see any errors. Remember that changes in bylaws and constitutions usually have a prescribed procedure for approval within each subgroup. We are committed to keeping this publication up to date, and we appreciate your input.
Georgia Library Association Handbook(s), October 30, 2020 and February 15, 2021. 2 PDF files.
Keywords: Electronic records; Georgia Library Association; Handbooks and manuals